Daily work-family conflict and alcohol use: testing the cross-level moderation effects of peer drinking norms and social support - Wang, Mo; Liu, Songqi; Zhan, Yujie; Shi, Junqi (Journal of applied psychology, 2010)
In the current study, we conducted daily telephone interviews with a sample of Chinese workers (N = 57) for 5 weeks to examine relationships between daily work-family conflict and alcohol use. Drawn from the tension reduction theory and the stressor-vulnerability model, daily work-family conflict variables were hypothesized to predict employees' daily alcohol use. Further, social variables (i.e., peer drinking norms, family support, and coworker support) were hypothesized to moderate the relationship between work-family conflict and alcohol use. Results showed that daily work-to-family conflict but not family-to-work conflict had a significant within-subject main effect on daily alcohol use. In addition, there was significant between-subject variation in the relationship between work-to-family conflict and alcohol use, which was predicted by peer drinking norms, coworker support, and family support. The current findings shed light on the daily health behavior consequences of work-family conflict and provide important theoretical and practical implications.